(untitled) (Indonesian Contemporary Nursing Journal (ICON Journal), 2024)
Aims: This study aimed to identify the validity and reliability of the core competencies of The Holistic Nursing Competency Questionnaire and The Holistic Needs of Patients. Methods: A pilot study with a correlational descriptive design was conducted to measure holistic nursing competency and the fulfillment of holistic patient needs in the ICU room of Dr. H. Soewondo Kendal Hospital. The study included 25 nurses and 30 patients. Holistic nursing competency was measured using a questionnaire, while the fulfillment of holistic patient needs was assessed using an observation sheet. Results: The Holistic Nursing Competency Questionnaire is valid, reliable, and psychometrically robust, but the holistic needs of patients were reduced from 33 items to 29 valid and reliable items. Conclusion: The validity test showed that the questionnaire and observation sheet were valid and reliable for measuring holistic nursing competency and the fulfillment of holistic patient needs. The study highlights the need to improve nurses’ holistic competencies and address the challenges in fulfilling the holistic needs of patients, especially in critical care areas.